Augmented reality for the surgeon: Systematic review. Issue 4 (30th April 2018) - Yoon, Jang W.; Chen, Robert E.; Kim, Esther J.; Akinduro, Oluwaseun O.; Kerezoudis, Panagiotis; Han, Phillip K.; Si, Phong; Freeman, William D.; Diaz, Roberto J.; Komotar, Ricardo J.; Pirris, Stephen M.; Brown, Benjamin L.; et al.
Abstract: Introduction: Since the introduction of wearable head‐up displays, there has been much interest in the surgical community adapting this technology into routine surgical practice. Methods: We used the keywords augmented reality OR wearable device OR head‐up display AND surgery using PubMed, EBSCO, IEEE and SCOPUS databases. After exclusions, 74 published articles that evaluated the utility of wearable head‐up displays in surgical settings were included in our review. Results: Across all studies, the most common use of head‐up displays was in cases of live streaming from surgical microscopes, navigation, monitoring of vital signs, and display of preoperative images. The most commonly used head‐up display was Google Glass. Head‐up displays enhanced surgeons' operating experience; common disadvantages include limited battery life, display size and discomfort. Conclusions: Due to ergonomic issues with dual‐screen devices, augmented reality devices with the capacity to overlay images onto the surgical field will be key features of next‐generation surgical head‐up displays.